Adipocyte-derived endotrophin promotes malignant tumor progression - Jiyoung Park; Philipp E. Scherer (The Journal of Clinical Investigation, 2012)
Adipocytes represent a major cell type in the mammary tumor microenvironment and are important for tumor growth. Collagen VI (COL6) is highly expressed in adipose tissue, upregulated in the obese state, and enriched in breast cancer lesions and is a stimulator of mammary tumor growth. Here, we have described a cleavage product of the COL6α3 chain, endotrophin (ETP), which serves as the major mediator of the COL6-mediated tumor effects. ETP augmented fibrosis, angiogenesis, and inflammation through recruitment of macrophages and endothelial cells. Moreover, ETP expression was associated with aggressive mammary tumor growth and high metastatic growth. These effects were partially mediated through enhanced TGF-β signaling, which contributes to tissue fibrosis and epithelial-mesenchymal transition (EMT) of tumor cells. Our results highlight the crucial role of ETP as an obesity-associated factor that promotes tumor growth in the context of adipocyte interactions with tumor and stromal cells.